Plasma testosterone and cortisol responses to prolonged sculling in male competitive rowers - Jurimae, J.; Jurimae, T.; Purge, P. (Journal of Sports Sciences, 2001)
In this study, we examined anabolic and catabolic hormone responses to a single endurance rowing training session in 12 male competitive single scull rowers. A work intensity eliciting a blood lactate concentration of 4 mmol(-1) was determined on a rowing ergometer during an endurance rowing training session lasting about 2 h (7891+/-761 s; distance covered 22.6+/-2.5 km; heart rate 136+/-7 beats x min(-1); intensity 77.4+/-3.8% of anaerobic threshold; mean +/- s). Venous blood samples were obtained before and after on-water rowing. Cortisol, testosterone and sex hormone binding globulin were measured and free testosterone and the free testosterone: cortisol ratio calculated. Blood lactate concentration did not change significantly during training (from 1.7+/-0.4 to 1.9+/-0.4 mmol x l(-1)); however, body mass was reduced (from 82.0+/-10.8 to 80.6+/-11.2 kg) and was related to the distance covered (r = -0.75). The concentrations of cortisol and testosterone did not change significantly during rowing or in the first 2 h of recovery. Free testosterone was reduced in the first 2 h of recovery, but no significant changes were observed in the free testosterone: cortisol ratio. Immediately after rowing, the concentrations of cortisol (r = 0.49) and free testosterone (r = -0.58) were related to the distance covered. Our findings indicate that a prolonged low-intensity training session results in a similar anabolic and catabolic hormone stimulus for trained rowers.